2017
DOI: 10.4103/jlp.jlp_127_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of galactomannan test with bronchoalveolar lavage and serum for the diagnosis of invasive aspergillosis in patients with hematological malignancies

Abstract: INTRODUCTION:Invasive pulmonary aspergillosis (IPA) is a major cause of morbidity and mortality in patients with hematological malignancies. In recent years, testing for values of galactomannan (GM) in serum and bronchoalveolar lavage (BAL) fluid has been investigated as a diagnostic test for IPA for such patients, but global experience and consensus on optical density (OD) cutoffs, especially for BAL galactomannan remains lacking.METHODS:We performed a prospective case–control study to determine an optimal BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…We have shown that in the ipsilateral ischemia core cortex, Iba-1 + cells are one of the main sources for the production of BDNF [ 7 ]. Other cell types, such as CD68 + microglia, and NeuN + neurons, are partly responsible for production of BDNF, even after the induction of ischemia.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that in the ipsilateral ischemia core cortex, Iba-1 + cells are one of the main sources for the production of BDNF [ 7 ]. Other cell types, such as CD68 + microglia, and NeuN + neurons, are partly responsible for production of BDNF, even after the induction of ischemia.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of allogeneic bone marrow MSC culture, cell transplantation, dMCAO model establishment, and behavioral tests have been described in our previous study [ 7 ]. In brief, 1 × 10 6 MSCs in 1 mL 0.9% saline were administered via intravenous injection one hour after ischemia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations